The Infection Returns: A Case of Pulmonary Sporotrichosis Relapse after Chemotherapy - Farooqui, Samid M. (Case Rep Med, 2018)
BACKGROUND: Pulmonary sporotrichosis is a rare disease caused by a dimorphic fungus, Sporothrix schenckii. It is rarely found in association with malignancy. We present a case of pulmonary sporotrichosis recurrence after chemotherapy. CASE PRESENTATION: A 44-year-old man, treated for pulmonary sporotrichosis in the past, presented with dysphagia and was found to have squamous cell carcinoma of the esophagus. After undergoing chemotherapy, extensive cavitary lesions were observed on thoracic computed tomography scan. A bronchoalveolar lavage revealed the presence of Sporothrix schenckii sensu lato. Despite treatment with itraconazole, he eventually required a left pneumonectomy for progressive destructive cavitary lesions involving the left lung. CONCLUSION: This case highlights the importance of considering past fungal infections, albeit cured, in patients initiating immunosuppressive therapy.